2014
DOI: 10.1016/j.msea.2013.10.094
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grain size distribution on the Hall–Petch relationship of welded structural steel

Abstract: The strength of polycrystalline metals increases with a decrease in grain size according to the HallPetch relationship. However, heterogeneous microstructures deviate from this relationship depending on the distribution of grain sizes. This paper introduces a rule of mixtures based approach for determining the characteristic length of the microstructure for heterogeneous weld metal. The proposed grain size parameter, the volume-weighted average grain size, is measured experimentally for nine structural steel w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(113 citation statements)
references
References 44 publications
8
101
0
4
Order By: Relevance
“…The average grain size, for example, is responsible for the so-called "Hall-Petch strengthening" [1,2] and is important for fatigue resistance [3,4]. The grain size distribution has similar effects, albeit generally less pronounced [5,6]. Of course, these phenomena are directly related to the stress and strain heterogeneities developing at the microstructure scale [7].…”
Section: Introductionmentioning
confidence: 99%
“…The average grain size, for example, is responsible for the so-called "Hall-Petch strengthening" [1,2] and is important for fatigue resistance [3,4]. The grain size distribution has similar effects, albeit generally less pronounced [5,6]. Of course, these phenomena are directly related to the stress and strain heterogeneities developing at the microstructure scale [7].…”
Section: Introductionmentioning
confidence: 99%
“…1. The grain size characterisation of heterogeneous weld metals was studied by Lehto et al [23]. The grain size measurements revealed that structural steel weld metals exhibit a large variety of grain size distributions that are noticeably broader than those of the base metal.…”
Section: Introductionmentioning
confidence: 99%
“…measured in this study. Based on the dates in Table 1 and interrelated counting, we figured out that yield strength of different positions is inversely proportional to the average grain size, and they are in keeping with Hall-Petch relation [16].…”
Section: Microstructure Of Test Platementioning
confidence: 56%
“…According to the strength expression formula raised by Pickering [16], the strength of matrix is express as: propagation [23], the resistance of crack propagation in coarse grain region is smaller. Therefore, it is apt to be the lower energy paths for crack propagation and connectivity, creating conditions for laminated tensile fracture.…”
Section: Discussionmentioning
confidence: 99%